PENGARUH METODE PEMBELAJARAN TEAM QUIZ BERBANTUAN PUZZLE TERHADAP PEMAHAMAN KONSEP IPAS PESERTA DIDIK KELAS V MADRASAH IBTIDAIYAH NEGERI 2 PRINGSEWU - Ahmad Rudi Nurcahyo; Chairul Amriyah; Hasan Sastra Negara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students’ understanding of Natural and Social Science (IPAS) concepts at the elementary school level remains relatively low due to learning processes that do not actively engage students and the limited use of varied instructional media. Learning activities that are dominated by the lecture method tend to make students passive and struggle to connect the material with real-life experiences. This condition results in low learning outcomes in the IPAS subject at Madrasah Ibtidaiyah Negeri 2 Pringsewu. This study was designed to address the issue of how significantly the Team Quiz learning method assisted by puzzle media influences the improvement of students’ conceptual understanding of IPAS.The purpose of this research is to determine the effectiveness of the Team Quiz method assisted by puzzle media in enhancing students’ ability to understand IPAS concepts through cooperative, competitive, and enjoyable learning activities. The research employed a quantitative approach with a Quasi-Experimental design of the Nonequivalent Control Group Design type. The subjects of the study involved two classes, namely class VA as the experimental group and class VB as the control group, with a total sample of 65 students. Data were collected through pretest and posttest instruments and analyzed using the t-test with SPSS 29 software.The results showed that there was a significant influence of the Team Quiz method assisted by puzzle media on students’ conceptual understanding of IPAS. Based on the t-test results using SPSS 29, the significance value obtained was 0.000 < 0.05, with the average posttest score of the experimental class (84.32) being higher than that of the control class (73.14). This finding proves that the Team Quiz method assisted by puzzle media is effective in improving the conceptual understanding of IPAS among fifth-grade students at Madrasah Ibtidaiyah Negeri 2 Pringsewu.